Possibility of treatment modification in patients with ankylosing spondylitis achieved of partial remission on treatment with adalimumab: Real practice data - A. V. Petrov; Ya. O. Shevnina; A. S. Gaffarova; N. V. Matveeva (Научно-практическая ревматология)
Objective. To assess the duration of remission or inactive disease status in patients with achieved partial remission due to treatment with adalimumab (ADA) after it discontinuation.Materials and methods. A dynamic observation was conducted of 26 patients with ankylosing spondylitis with partial remission achieved due to prolonged use (for 24 months or more) of subcutaneous injections of 40 mg ADA once every two weeks. The discontinuation of ADA was carried out after a 3-4 month period of its use in de-escalation mode in the form of 1 injection (40 mg) once every 4 weeks. After discontinuation of ADA, patients continued to take non-steroidal anti-inflammatory drugs, sulfasalazine at a dose of 1.5-2 g per day (11 patients) and methotrexate 10 mg per week (3 patients). Assessment of the clinical, laboratory and ultrasonographic parameters of ankylosing spondylitis was carried out in 3, 6 and 12 months after the abolition of the ADA.Results and discussion. Among the observed patients, partial clinical remission of ankylosing spondylitis maintained after 6 months in 12 (46.2%) patients, and after 12 months - in 10 (38.5%). A low degree of ankylosing spondylitis activity (BASDAI <4) was maintained for 6 months after the abolition of ADA in 14 (53.8%) patients, and after 12 months - in 12 (46.2%).Conclusion. Within 12 months after cancellation of ADA, ankylosing spondylitis exacerbation was observed in 53.8% of patients with initially achieved partial clinical remission.